Revolutionizing the stage: exploring the multidimensional landscape of digital theater. - Ma, Ming; Yuping, Kang (Digital Scholarship in the Humanities, 2025)
This study explores the transformative effects of digital technologies on the traditional stage and examines the multifaceted nature of digital theater (DT). It clarifies the concept of DT by identifying its essential attributes and establishing an analytical framework for its classification, based on the interplay of three critical dimensions: artistic creation, digital technology, and audience experience. This article uses this analytical framework to explore the diversity of DT, including live theater, cyber theater, and mixed theater, analyzing how these forms enhance audience immersion and participation through technological means. Additionally, this article systematically examines the production logic of DT by analyzing each stage of the production process. The study also discusses the future challenges of DT, including managing technical costs, promoting content innovation, securing audience engagement, enforcing copyright protection, and improving professional talent training. It highlights the transformative potential of DT in redefining the theatrical experience and performance ecology, emphasizing the convergence of art and technology in shaping the future of theater.